Effects of stress conditions on plasma parameters and gene expression in the skin mucus of farmed rainbow trout (Oncorhynchus mykiss) - Fiordelmondo, Elisa; Magi, Gian Enrico; Friedl, Adina; El-Matbouli, Mansour; Roncarati, Alessandra; Saleh, Mona (Frontiers in Veterinary Science, 2023)
The aim of this study was to investigate the physiological response of rainbow trout (Oncorhynchus mykiss) before slaughtering in the last phase of farming analyzing skin mucus and plasma. Two groups of rainbow trout were considered: Group UN ("unstressed"), represented by fish randomly captured from raceways, in the last phase of a standard fattening cycle; Group S ("stressed"), collected at the end of the pre-slaughtering tank, soon after slaughtering. The fish skin mucus was swabbed from head to tail using a sterile plastic spatula and the blood was collected through an endocardial puncture. qRT-PCR was used to study the gene expression in skin mucus. The mRNA expression levels of the IL-6 and IgD genes were higher in the S than in the Group UN. The plasma analysis showed an only a decrease in the glucose plasma levels in the Group S when compared to the Group UN. The present results indicated that the procedures adopted after slaughtering only affected change ha eliminato: H 26 ha eliminato: healthy 27 ha eliminato: H 28 ha eliminato: H 29 ha eliminato: the only 30 2 plasma glucose and skin mucus activity in rainbow trout suggesting that management protocol was compatible with non-stressful farming conditions.